Relationship Of Mother Knowledge 1000 HPK, Parenting and Dietary Habit With Babies 6-24 Months Nutrition Status In Cilangkahan Malimping Lebak - Ahmad Faridi (Jurnal Gizi dan Pangan Soedirman, 2020)
Age 0–24 months is the age group that is experiencing critical growth. Therefore, the handling of malnutrition in this age group (0–24 months) is of greater concern because if it is not handled properly it can suffer growth failure. The purpose of this study was to determine the relationship between maternal knowledge, parenting and diet with the nutritional status of infants 6-24 months. This study used a cross sectional design and the sampling was carried out by total sampling with a total of 47 babies aged 6-24 months. The data were taken from June to August 2020. The research data obtained were based on the results of questionnaires and a 24-hour food recall. The statistical data analysis used was the chi-square test. There is no relationship between maternal knowledge and nutritional status, there is a relationship between parenting and diet with nutritional status p = 0.032 and p = 0.026